LA RELACIÓN ENTRE LA AFECTIVIDAD Y COMPORTAMIENTO ACADÉMICO DE LOS NIÑOS Y NIÑAS, DEL CUARTO AÑO DE EDUCACIÓN BÁSICA PARALELO “A” DE LA UNIDAD EDUCATIVA “Dr. GERMAN ABDO TOUMA”, RIOBAMBA, PERÍODO 2017 – 2018. - Simbaina Guamán, Alex José (2019)
This research was carried out with the purpose of demonstrating the influence of affectivity on the academic behavior of children in the Basic General Education room of the "German Abdo Touma" Educational Unit. Because it managed to identify the consequences of the lack of affectivity in children, with the purpose of socializing with people immersed in this problem: fathers and mothers, students and teachers, it has a qualitative approach, because it was a Inquiry of a social nature was carried out without deliberately manipulating any variable, where the facts were observed as they were presented in their real context, it was also based on a diagnostic - exploratory way, because it allowed us to observe the results of affectivity, behavior, family problems, academic situation that the children are going through within their educational establishment, the population of the Basic General Education students of the German Abdo Touma Educational Unit, the sample was not probabilistic and intentional because they worked with the 22 children and 16 girls, the technique was the observation with his instrument the observation sheet, the same q It helped to carry out the adequate analysis and interpretation of the data, after the analysis and interpretation it was concluded that it was observed that the children did develop their affectivity before their peers, teachers and parents, because they are solidarity in situations outside of them, which favors the behavior within the classroom that particularly present all their duties among others.